Global burden of age-related macular degeneration (1990–2021): trends, age-sex disparities, and socioeconomic dynamics from the GBD study - Kong, Haorong; Feng, Hui; Wang, Hong (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to assess the global burden of Age-related macular degeneration (AMD) across countries, regions, and age groups by sex, sociodemographic index (SDI) level, and risk factors from 1990 to 2021, using newly updated data from the Global Burden of Disease (GBD) study. The focus was on age-related disparities in AMD burden by sex and SDI.MethodsThis population-based study utilized AMD data from GBD 2021 (1990–2021). The burden was evaluated using the number of cases, prevalence rates per 100,000 population, and trends in years lived with disability (YLDs) and prevalence, assessed through average annual percentage changes (AAPCs) and estimated annual percentage changes (EAPCs).ResultsGlobally, AMD prevalence increased from 364,000 cases in 1990 to 806,000 in 2021 (+121%), while YLDs rose from 30,000 to 58,000 (+91%). However, age standardized prevalence and YLD rates (ASPRs and ASYRs) significantly declined (EAPCs: −0.26 and −0.94, respectively). Regional analyses revealed that low SDI regions (e.g., sub-Saharan Africa) bore the highest AMD burden (ASPR: 139.9 per 100,000) and exhibited a younger age distribution, with a significantly higher proportion of cases in individuals aged 55–74 years. In contrast, high SDI regions (e.g., high-income Asia-Pacific) had a concentration of cases among those aged 70 years or older. While medium SDI regions accounted for one-third of global cases in 2021, age-standardized rates declined most slowly in low SDI regions (EAPC: −1.03) and even trended upward in some countries. AMD cases peaked globally at ages 65–69, yet prevalence was highest among those over 85 years (1,349.9 per 100,000), with women generally experiencing a higher burden than men. These findings highlight distinct regional patterns, with younger disease profiles in low SDI regions and aging-driven increases in high SDI regions, underscoring the need for targeted prevention and control strategies.ConclusionAlthough global efforts over the past 30 years have led to a decline in AMD prevalence rates and YLDs, the absolute number of cases and YLDs continues to rise, driven by age, sex, socioeconomic status, and geographic location. These findings provide an epidemiological basis for developing global public health strategies to address these ongoing challenges.